Biosynthesis, structure, and folding of the insulin precursor protein. (19th September 2018) - Liu, Ming; Weiss, Michael A.; Arunagiri, Anoop; Yong, Jing; Rege, Nischay; Sun, Jinhong; Haataja, Leena; Kaufman, Randal J.; Arvan, Peter
Abstract : Insulin synthesis in pancreatic β‐cells is initiated as preproinsulin. Prevailing glucose concentrations, which oscillate pre‐ and postprandially, exert major dynamic variation in preproinsulin biosynthesis. Accompanying upregulated translation of the insulin precursor includes elements of the endoplasmic reticulum (ER) translocation apparatus linked to successful orientation of the signal peptide, translocation and signal peptide cleavage of preproinsulin—all of which are necessary to initiate the pathway of proper proinsulin folding. Evolutionary pressures on the primary structure of proinsulin itself have preserved the efficiency of folding ("foldability"), and remarkably, these evolutionary pressures are distinct from those protecting the ultimate biological activity of insulin. Proinsulin foldability is manifest in the ER, in which the local environment is designed to assist in the overall load of proinsulin folding and to favour its disulphide bond formation (while limiting misfolding), all of which is closely tuned to ER stress response pathways that have complex (beneficial, as well as potentially damaging) effects on pancreatic β‐cells. Proinsulin misfolding may occur as a consequence of exuberant proinsulin biosynthetic load in the ER, proinsulin coding sequence mutations, or genetic predispositions that lead to an altered ER folding environment. Proinsulin misfolding is a phenotype that is very much linked to deficient insulin production and diabetes, as is seen in a variety of contexts: rodent models bearing proinsulin‐misfolding mutants, human patients with Mutant INS ‐gene‐induced Diabetes of Youth (MIDY), animal models and human patients bearing mutations in critical ER resident proteins, and, quite possibly, in more common variety type 2 diabetes.